The study of electrical conductivity of ABS reinforced carbon black blends: article - Wan Rosli, Wan Muhammad Nadzmi; Alauddin, Sakinah (2019)
Acrylonitrile-butadiene-styrene (ABS) is a synthetic engineering resin that is widely used worldwide in various industries. ABS is known for its physical properties and capable to become electrical conductor. Naturally, ABS exist as insulating behavior thus carbon black (CB) were introduced into ABS matrix to change its behavior from insulation to conducting behavior. Electrical conductivity of ABS reinforced carbon black blends was study. Electrical conductivity of ABS reinforced CB blends will be determined by taking the weight percent (wt%) content of carbon black at various ranging from 10 wt% to 50 wt%. Besides that, effect of temperature on electrical conductivity were also investigated. Various temperature ranging from room temperature to 100⁰c were used. Increasing CB content in the blends create higher conductivity. Conductive network created by conductive filler has change the ABS matrix thus increase the electrical conductivity of ABS. Introducing more CB content will produce ABS and CB blends with higher conductivity. The temperature also plays a major role in order to achieve higher conductivity. As the temperature increase the conductivity of ABS CB blends will also increase.